Al-Tamadhhub al-Fiqhī wa-Ḥifẓ al-Ḍarūriyyāt al-Khams bayna al-Waḥdah wa-al-Taʿaddud: Dirāsah fī Ikhtilāfāt al-Fuqahāʾ - Yusuf Usman; Bishir Salis Idris (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2025)
This study examines adherence to juridical madhhab and its role in preserving the five essential objectives (al-ḍarūriyyāt al-khams) of Islamic law between unity and plurality, through an analytical study of juristic disagreement. It addresses the prevailing assumption that madhhab-based reasoning constitutes an obstacle to legal reform and promotes doctrinal rigidity. The study argues instead that madhhabism represents a disciplined methodological framework that historically regulated legal disagreement, structured juristic reasoning, and safeguarded the higher objectives (maqāṣid) of the Sharīʿa from fragmentation and arbitrary interpretation. Employing an inductive-analytical method combined with comparative analysis across the four Sunni legal schools, the study draws on classical works of fiqh, uṣūl al-fiqh, and maqāṣid al-sharīʿa. Selected cases related to the preservation of religion, life, intellect, lineage, and property demonstrate that juristic plurality does not signify divergence in legal objectives or a violation of foundational principles. Rather, it reflects diverse interpretive mechanisms aimed at realizing shared higher goals within varying historical and social contexts. The study concludes that adherence to madhhab remains a normative and practical mechanism for balancing unity at the level of objectives with plurality at the level of legal interpretation, reaffirming its relevance in contemporary Islamic legal discourse.